2022
DOI: 10.1155/2022/5602011
|View full text |Cite
|
Sign up to set email alerts
|

Calbindin S100A16 Promotes Renal Cell Carcinoma Progression and Angiogenesis via the VEGF/VEGFR2 Signaling Pathway

Abstract: Purpose. Recent research has indicated that the calcium-binding protein S100A16 promotes carcinogenesis and tumor growth in several forms of cancer. e objective of this study was to examine the relationship between S100A16 and renal cell cancer. Methods. By using e Cancer Genome Atlas (TCGA) database, the differentially expressed gene S100A16 was identified, and its appearance and link to the prognosis of persons with renal cancer were confirmed. Cox regression was used in multivariate analysis, and a nomogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…S100A16 is predominantly localized in the cytoplasm of cells, where S100A16 can interact with a variety of target proteins, including signaling molecules and cytoskeletal components. These interactions can modulate cellular processes and affect various signaling pathways [21][22][23]. Some studies have suggested that S100A16 was involved in promoting cell proliferation, metastasis, and tumor growth in certain cancers, including prostate cancer and esophageal squamous cell carcinoma [24].…”
Section: Discussionmentioning
confidence: 99%
“…S100A16 is predominantly localized in the cytoplasm of cells, where S100A16 can interact with a variety of target proteins, including signaling molecules and cytoskeletal components. These interactions can modulate cellular processes and affect various signaling pathways [21][22][23]. Some studies have suggested that S100A16 was involved in promoting cell proliferation, metastasis, and tumor growth in certain cancers, including prostate cancer and esophageal squamous cell carcinoma [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that the upregulation of key gene targets under TRPV6 suppression or overexpression indicates that TRPV6 plays a crucial role via calcium signaling in angiogenesis, required for dissemination of prostate cancer cells to both adjacent and distant tissues. Indeed, several studies have reported that calcium signaling in cancer cells was linked to the angiogenic phenotype (Cui et al, 2017;Wang N. et al, 2022) via either the expression of hypoxia-inducible factor 1-alpha (HIF1ɑ) (Kim et al, 2015;Ma et al, 2018) or secretion of the vascular endothelial growth factor (VEGF), or inducing calcium oscillations in endothelial cells while binding to VEGF receptors (Wang N. et al, 2022;, or inducing cell proliferation, migration, and invasion needed to form new vessels. TRP channels, known to be environmental sensors and permeable to calcium, modulate intracellular calcium concentrations and participate in the initiation and progression of cancers Bai et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The authors further demon-strated that knockdown of S100A16 suppressed cell proliferation and invasion abilities in RCC cells. These functional effects were suggested to be associated with inhibition of VEGF, VEGFR2, and pAkt in RCC cells with S100A16 knockdown [32].…”
Section: Renal Cell Carcinomamentioning
confidence: 96%
“…Using the TCGA transcriptome dataset, Wang et al identified S100A16 mRNA to be significantly up-regulated in renal cell carcinoma (RCC) specimens as compared to noncancerous tissues [32]. High expression of S100A16 mRNA in RCC specimens was suggested to be associated with poor overall survival, progression-free interval, and diseasespecific survival.…”
Section: Renal Cell Carcinomamentioning
confidence: 99%